The role of Lipata Port in the enhancement of Culasi, Antique (1986-2001). - Ruiz, Selly V.
This study describes the role of Lipata Port in the enhancement of the municipality of Culasi, Antique (1986-2001). The study was conducted in Culasi, Antique particularly in Barangay Lipata where the port is located. Informants of the study were selected based on their knowledge and understanding on the information being sought. The number of informants is not vital in the study., The results of the interviews were crosschecked using multiple sources. The study concludes that Lipata Port had brought various benefits in the municipality of Culasi, Antique. It had contributed a significant share in the promotion of the socio-cultural, political and economic life of Culasinos. The researcher recommends that further research should be conducted about the impact of Lipata Port to the people of Culasi using open-ended questionnaires for a more substantial analysis and valid report on the role of Lipata Port in the municipality of Culasi, Antique.